Disclosure and representation of transactions with related parties of companies listed on B3: a look at corporate governance - Weingärtner, Natália; Souza, Maíra Melo de (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Purpose: Analyze the level of disclosure and representativeness, understood as the degree to which transactions with related parties are treated, monitored and disclosed in corporate governance practices, considering aspects such as the detail required by CPC 05 (R1) and IAS 24, of the companies involved in B3. Methodology: Two checklists were developed to analyze related-party transactions (RPTs) and corporate governance. The sample analyzed consisted of 315 companies that had RTPs in 2022. Results: The results demonstrated that companies with better corporate governance practices presented greater detail and representativeness in the disclosure of TPR, with greater adherence to the requirements of CPC 05 (R1) and IAS 24, evidencing compliance with additional requirements related to transparency and comparability of information. Contributions of the Study: The analysis revealed a positive and statistically significant correlation between the level of corporate governance and the level of disclosure and representativeness of TPR, indicating that companies with more robust governance structures tend to present more complete and detailed disclosures, in compliance with applicable standards.